KONTRIBUSI MINAT SISWA TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SISWA KELAS XI DI SMA NEGERI 1 BAGAN SINEMBAH - Cues Ardanata; Ni Putu Nita Wijayanti; Syahriadi Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the low interest in learning physical education, which makes the learning outcomes achieved very unsatisfactory. The aim of this research was to determine students' interest in the learning outcomes of physical education. The population in this research were students from SMA Negeri 1 Bagan Sinembah using a purposeful sampling technique, 23 students in total. The instrument used in this research is the use of a questionnaire completed by students. Based on the results of a simple correlation test, it is obtained that R-count = 0.839 > Ftable = 0.432 at = 5% with dk (n-1 = 22), which means that the test is significant, so that (Ha) it says , is a relationship between students' interest in learning outcomes of physical education and sports Health of class Xi students at SMA Negeri 1 Bagan Sinembah.Keywords: student interest, learning outcomes, physical education